Oblicz: (-2)×6+4:(-8)+4²+(14)³=
(-236)×12²+22×(-2)-98³=
16×(4²-(-4)²)+25:5²-10⁰=
100⁰:6+(-1)⁴-7+2³-2²×2=
50:(15:3)100×-10+2×5-2³:4=
120×(240):(-12)=
80:40:5+(-2)×(-3)-(-1)×(-6)+2⁴:(-4)=
12:2×3-6×1+6⁰+12+(-122)=

Tylko plz nie samee wyniki ;p

2

Odpowiedzi

2010-02-27T13:28:04+01:00
(-2)×6+4÷(-8)+4²+(-14)³=-12+4÷(-8)+16+(-2744)=12+(-0,5)+16+(-2744)=2716,5
2010-02-27T13:34:31+01:00
(-2)×6+4:(-8)+4²+(14)³=-12+4:(-8)+16+2744= 1+16+2744+=2761
(-236)×12²+22×(-2)-98³=(-236)x144-44-941192=-33984-941236=975220
16×(4²-(-4)²)+25:5²-10⁰= 16x(16-16)+25:25-1=0+1-1=0
100⁰:6+(-1)⁴-7+2³-2²×2=1\6+1-7+8-8=-5 5\6
50:(15:3)100×-10+2×5-2³:4= 50:5x100x-20-2=1000x(-22)= -22000
120×(240):(-12)= 28800:(-12)= -2400
80:40:5+(-2)×(-3)-(-1)×(-6)+2⁴:(-4)= 2/5 + 6-6-4= -3 3/5
12:2×3-6×1+6⁰+12+(-122)= 18- 7+12-122=11-110=-99